Capoeira e temas transversais: Avaliação de um blog didático para as aulas de educação física - Suraya Cristina Darido; Luiz Gustavo Bonatto Rufino; Luciana Maria Fernandes Silva (Universidade Estadual de Campinas, 2013)
The Internet nowadays is a significant source of information, being important the construction of educational sites resulting from scientific research to foster pedagogical reflections. It is also important to support possibilities of relations between transversal themes, big problems of society that must be contextualized in school, in educational practice. In Physical Education, capoeira, part of the movement body culture, should also be addressed during the pedagogical practice. We evaluated a blog developed to address the Transversal Themes and Capoeira, taking into consideration the opinions of 23 teacher participants (12 women and 11 men, mean age 30 years). We opted for qualitative research and analysis of content from a questionnaire developed to evaluate the blog. The analysis was divided into two categories: presentation of the educational blog developed and analysis of results from the evaluation of participants, this category being divided into three subcategories: opinions about the design and configuration of the blog, interest and motivation; considerations about the transversal themes. The results were positive in terms of consistency, language, appropriateness of content to the topic and audience, visualization, reliability and conceptual rigor of the blog. All participants said they could use the content proposed in the blog for the development of their classes. From these results, it is considered that the blog can become a virtual educational material, assisting teachers in the teaching-learning process, helping the didactic process in Physical Education classes.